The co-existence between DSE and AMF symbionts affects plant P pools through P mineralization and solubilization processes - Della Mónica, Ivana Florencia (2015)
The capacity of dark septate endophytes (DSE; Phialocephala turiciensis, Acephala applanata, P. glacialis and Phaeomollisia piceae) to solubilize inorganic phosphate (P) and to mineralize the organic form was studied. We analysed the effect of DSE strains on P uptake by Trifolium repens in the presence or absence of arbuscular mycorrhizal fungi (AMF). Phosphatases were observed both in the absence of the host plant and the organic resource, showing that the P mineralization process is not induced by the enzyme substrate or the host. DSE were more efficient at mineralizing organic P. Independently of the presence of AMF, DSE increased the pool of P in the soil, with significant differences being found in P levels among the different DSE. In contrast, plant P uptake was increased by AMF. The P content of plants increased with the co-inoculation of AMF and P. turiciensis or P. piceae. We hypothesize a close relationship between DSE and AMF in relation to P availability and uptake in plants. Whereas DSE increase the pool of P in the rhizosphere, AMF are responsible for P transfer to the host, with co-colonization of plants by DSE and AMF showing a synergistic outcome.